Assessment of Immunologic Responses in Khaki Cambell Ducks Vaccinated Against Duck Plague - Islam, M.A.; Samad, M.A.; Rahman, M.B.; Hossain, M.T.; Akter, S. (International Journal of Poultry Science, 2004)
The duck plague vaccine (DPV) is locally produced from the Livestock Research Institute (LRI), Mohakhali, Dhaka which is used to control the duck plague viral disease in ducks in Bangladesh. Efficacy of this vaccine reports has no, so to say on ducks in Bangladesh. Three weeks old 50 Khaki Cambell Ducks were used to evaluate the induced of immune responses of duck plague vaccine during the period from February to April 2003. These 50 ducks were divided into three groups (A = 15, B = 15 and C = 5 ducks) and each duck of group A and group B were inoculated primarily with duck plague vaccine @ 1.0 ml. intramuscularly at the age of 4 weeks and whereas ducks of group C served as unvaccinated control. Then each duck of group A was also injected booster dose after 2 weeks of primary vaccination with same vaccine, dose and route. The mean value of TLC, TSP and PHA antibody titre of ducks of group A was found significantly (p < 0.1) increased at two weeks and four weeks of post-primary vaccination and two weeks and four weeks of post-booster vaccination in comparison to the pre-vaccination values. The mean value of TLC, TSP and PHA titre of ducks of group B was also found significantly increased (p < 0.1) at two, four, six and eight weeks of post-primary vaccination in comparison to the pre-vaccination values. These results indicate that booster vaccination of duck plague vaccine induced comparatively higher TLC, TSP and PHA antibody titre than single primary vaccination in ducks. The mean value of TLC, TSP and PHA in unvaccinated control group C was more or less nearer at the age of four weeks and 12 weeks in ducks. These results showed that the locally prepared duck plague vaccine induced sufficient both cellular and humoral immune responses with booster-vaccination than primary vaccination in ducks. Therefore, it could be recommended to booster dose of vaccination of duck plague vaccine to control duck plague under field condition in Bangladesh.